Composite member, and method for manufacturing the same

The composite member with undulating groove edges in both vertical and in-plane directions addresses the challenge of achieving consistent high bonding strength across different force directions, resulting in improved durability and vibration resistance.

JP2025060016APending Publication Date: 2025-04-10RIKEN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170495
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing composite members with metal and resin portions face challenges in achieving high bonding strength regardless of the direction of the force applied, due to variations in bonding strength based on the direction of the force relative to the grooves on the metal surface.

Method used

The composite member features a metal portion with a joint surface containing a plurality of grooves, where each groove has undulating pair of edges in both the vertical and in-plane directions. This design enhances the anchoring effect of the resin within the grooves and concave portions, resulting in improved bonding strength in both vertical and in-plane directions.

Benefits of technology

This configuration allows for high bonding strength to be achieved consistently across various directions of force application, enhancing the durability and vibration resistance of the composite member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060016000001_ABST
    Figure 2025060016000001_ABST
Patent Text Reader

Abstract

To provide a composite member which can easily obtain high bond strength without depending on a direction of force applied between a resin part joined to a joint surface of a metal part provided with a plurality of groove parts and the composite member, in the joint surface.SOLUTION: A composite member includes a metal part, and a resin part. The metal part has a joint surface in which a plurality of groove parts are arrayed, and each of the respective groove parts constituting the plurality of groove parts has a pair of edge parts undulated in a vertical direction of an in-plane direction of the joint surface along an extension direction of the groove part.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite member in which a metal part and a resin part are joined together. [Background technology]

[0002] From the viewpoint of reducing the weight of various parts, resin members are sometimes used as substitutes for metal members. However, with resin members, it may be difficult to ensure performance such as thermal conductivity, which is disadvantageous to resin compared to metal. In contrast, composite members that combine metal and resin together can achieve weight reduction by using resin while taking advantage of the strengths of metal. However, with such composite members, it is difficult to obtain high joint strength between metal and resin, which are different materials.

[0003] Patent Document 1 discloses a technique for improving the bonding strength between metal and resin. In the technique described in Patent Document 1, a groove is provided in advance by scanning a laser on the bonding surface of the metal member to which the resin is to be bonded by insert molding. As a result, the resin enters the groove provided on the bonding surface of the metal member during insert molding, and the bonding strength of the resin to the bonding surface of the metal member can be increased by the anchor effect. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-064659 A Summary of the Invention [Problem to be solved by the invention]

[0005] Although the technique of providing a groove on the joining surface of the metal member as described above can easily improve the joining strength of the resin to the joining surface, the degree of improvement in the joining strength is likely to vary depending on the direction of the force applied between the joining surface and the resin. In other words, with the above technique, it is easy to improve the joining strength between the joining surface and the resin against a force in a direction along the groove, but it is difficult to improve the joining strength against a force in a direction perpendicular to the groove.

[0006] In view of the above circumstances, an object of the present invention is to provide a composite member in which high bonding strength can be easily obtained at the bonding surface of a metal part having a plurality of grooves, regardless of the direction of force applied between the metal part and a resin part bonded to the bonding surface. [Means for solving the problem]

[0007] In order to achieve the above object, a composite member according to one embodiment of the present invention includes a metal part and a resin part. The metal part has a joint surface on which a plurality of grooves are arranged, and each of the plurality of grooves has a pair of edges that rise and fall in the perpendicular and in-plane directions of the joint surface along the extension direction of the groove. The resin portion is directly bonded to the bonding surface.

[0008] In this composite material, in the joining surface of the metal part provided with the multiple grooves, in response to the force applied between the resin part directly joined to the joining surface, an anchor effect is obtained by the resin part entering the multiple grooves, and an anchor effect is also obtained by the resin part entering the recesses constituting the uneven shape provided on a pair of edges of each groove. As a result, in this composite material, a high joining strength is obtained between the metal part and the resin part, especially in the vertical direction.

[0009] Furthermore, in this composite material, by providing multiple grooves on the joining surface of the metal part, the restraining force in the extending direction of the grooves applied from the joining surface to the resin part is increased, thereby improving the joining strength in the extending direction of the grooves in the in-plane direction between the metal part and the resin part.

[0010] Furthermore, in this composite member, by configuring the uneven shape at each edge of each groove to undulate in the vertical direction, the binding force applied from the joining surface to the resin part in the in-plane direction perpendicular to the groove is increased, thereby improving the joint strength between the metal part and the resin part in the in-plane direction perpendicular to the groove. Also, in this composite member, by configuring the uneven shape at each edge of each groove to undulate in the in-plane direction, an anchor effect is obtained by the resin part penetrating into each recess of each edge in the in-plane direction, thereby further improving the joint strength between the metal part and the resin part in the in-plane direction perpendicular to the groove.

[0011] In this manner, with this composite material, high joint strength is easily obtained regardless of the direction of the force applied between the metal part and the resin part, which provides the composite material with high durability against various forces as well as high vibration resistance.

[0012] In a cross section of the composite member perpendicular to the extending direction, a length of the joining surface within a range of a predetermined dimension in the in-plane direction may be 150% or more of the predetermined dimension. The metal portion may contain any one of aluminum, iron, and copper as a main component. The resin portion may be mainly composed of a thermoplastic resin. The resin portion may contain a component that suppresses transmission of electromagnetic waves. The composite member may be configured as a case for an electronic device to be mounted in a vehicle.

[0013] In a method for manufacturing a composite member according to one embodiment of the present invention, a raw material metal having a joining surface and a raw material resin containing a thermoplastic resin as a main component are prepared. By providing a plurality of grooves arranged on the joining surface by laser processing, a metal component is produced in which each of the plurality of groove portions has a pair of edges that rise and fall in the perpendicular and in-plane directions of the joining surface along the extension direction of the groove portion. A composite member is produced by insert molding the raw resin using the metal member as an insert material, with a resin portion directly bonded to the bonding surface.

[0014] The metal member may be fabricated so that the ratio Sa / B of the average depth Sa to the average width B in each of the plurality of grooves is 0.2 or more. The metal member may be manufactured so that a ratio Sa / C of an average depth Sa of each of the plurality of grooves to a center line distance C of the plurality of grooves is 0.02 or more. Effect of the Invention

[0015] As described above, in the composite material of the present invention, high bonding strength is likely to be obtained at the bonding surface of the metal part having a plurality of grooves, regardless of the direction of force applied between the metal part and the resin part bonded to the bonding surface. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a perspective view of a composite member according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing only the metal portion of the composite member. [Diagram 3] 2 is a partial cross-sectional view of the composite member taken along line III-III' in FIG. 1. [Figure 4] 4 is a partial cross-sectional view of the composite member taken along line IV-IV' in FIG. 3. [Diagram 5] 4 is a partial cross-sectional view of the composite member taken along line VV' in FIG. 3. [Figure 6] 1 is a flowchart showing a method for manufacturing a composite member according to an embodiment of the present invention. [Figure 7] 1A to 1C are diagrams showing a process of performing laser processing on the joining surfaces of metal members. [Figure 8] 11 is a diagram showing the configuration of a groove portion of a metal member before insert molding. FIG. [Figure 9] 11 is a diagram showing the configuration of a groove portion of a metal member before insert molding. FIG. [Figure 10] 1A and 1B are diagrams showing an example in which the composite member is configured as a case for an electronic device to be mounted in a vehicle. [Figure 11] FIG. 2 is a perspective view of a sample of a composite member produced in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In each drawing, an X-axis, a Y-axis, and a Z-axis are shown as appropriate. The X-axis, the Y-axis, and the Z-axis are common to all the drawings.

[0018] [Configuration of composite member 1] FIG. 1 is a perspective view of a composite material 1 according to an embodiment of the present invention. The composite material 1 has a metal part 10 and a resin part 20. Both the metal part 10 and the resin part 20 are flat plates extending along the XY plane. In the composite material 1, the metal part 10 and the resin part 20 are laminated in the Z-axis direction, and the resin part 20 is directly bonded to a joint surface 11 provided on the metal part 10 and extending along the XY plane. In this embodiment, the direction in which the joint surface 11 extends as a whole (the direction along the XY plane in the example shown in FIG. 1, etc.) is also referred to as the in-plane direction of the joint surface 11, and the direction perpendicular to the joint surface 11 (the Z-axis direction in the example shown in FIG. 1, etc.) is also referred to as the perpendicular direction of the joint surface 11.

[0019] The metal part 10 may be made of any metal, and preferably has any one of aluminum, iron, and copper as the main component. The resin part 20 may be made of any resin, and preferably has a thermoplastic resin as the main component, because insert molding is possible. Examples of the thermoplastic resin as the main component of the resin part 20 include polybutylene terephthalate (PBT), polyphenylene sulfide (PPS), liquid crystal polymer (LCP), aliphatic polyamide, anti-aromatic polyamide, aromatic polyether ketone (including polyether ether ketone (PEEK), polyaryl ether ketone (PAEK), etc.), polyacetal (POM), polyetherimide (PEI), polycarbonate (PC), etc. In this embodiment, the "main component" refers to the component with the highest content ratio (wt%). The resin part 20 may be mixed with various fillers for the purpose of improving strength, imparting electromagnetic wave absorption and electromagnetic wave reflection, etc.

[0020] 2 is a perspective view showing only the metal part 10 with the resin part 20 removed from the composite material 1 shown in FIG. 1. A plurality of grooves 12 are provided on the joint surface 11 of the metal part 10. The plurality of grooves 12 each extend along the Y-axis direction and are arranged at intervals from each other in the X-axis direction. In the composite material 1 shown in FIG. 1, the resin part 20 is bonded to the joint surface 11 of the metal part 10 in a state of being in close contact with the joint surface 11 of the metal part 10, that is, being inserted into each groove 12. In this embodiment, the direction in which each groove 12 extends as a whole (the Y-axis direction in the example shown in FIG. 2 etc.) is also referred to as the extension direction of each groove 12.

[0021] FIG. 3 is a partial cross-sectional view of the composite member 1 taken along line III-III' in FIG. 1. FIG. 3 shows an enlarged view of the joint surface 11 of the metal part 10 in the composite member 1 and its vicinity. Each groove 12 has a pair of edges 12a extending along the Y-axis direction and a central part 12b recessed in the Z-axis direction between the pair of edges 12a. FIG. 4 is a partial cross-sectional view of the composite member 1 taken along line IV-IV' in FIG. 3. That is, FIG. 4 shows an enlarged view of a region including the edge 12a of the groove 12 in a cross section of the composite member 1 taken along the YZ plane. FIG. 5 is a partial cross-sectional view of the composite member 1 taken along line V-V' in FIG. 3. That is, FIG. 5 shows an enlarged view of a region including the edge 12a of the groove 12 in a cross section of the composite member 1 taken along the XY plane.

[0022] 4 and 5, each edge 12a of each groove 12 has an uneven shape in which undulations are repeated in both the Z-axis direction and the X-axis direction along the Y-axis direction. That is, each edge 12a of each groove 12 has recesses 12c recessed in the Z-axis direction and the X-axis direction constituting the uneven shape, arranged along the Y-axis direction. In each edge 12a of each groove 12, the resin part 20 is in close contact with the uneven shape, that is, the resin part 20 is embedded in each recess 12c.

[0023] With this configuration, in each groove 12 of the composite material 1, in addition to the anchor effect due to the resin part 20 entering the center part 12b in the Z-axis direction, an anchor effect is also obtained due to the resin part 20 entering the recesses 12c of each edge part 12a. As a result, in the composite material 1, the joint strength against a force applied mainly in the peeling direction along the Z-axis between the metal part 10 and the resin part 20 is improved due to a synergistic effect of the anchor effect in the center part 12b and the anchor effect in each recess 12c of each edge part.

[0024] Furthermore, by providing central portions 12b that are significantly recessed in the Z-axis direction in the multiple grooves 12 extending in the Y-axis direction on the joint surface 11 of the metal part 10, the joint surface 11 becomes a curved surface that rises and falls in the Z-axis direction along the X-axis direction, and the contact surface with the resin part 20 is expanded in a direction perpendicular to the Y-axis. As a result, in the composite member 1, the restraining force in the Y-axis direction applied from the joint surface 11 to the resin part 20 increases, improving the joint strength against a sliding force along the Y-axis applied between the metal part 10 and the resin part 20.

[0025] Furthermore, by providing each edge 12a of each groove 12 on the joint surface 11 of the metal part 10 with an uneven shape that rises and falls in the Z-axis direction along the Y-axis direction, the contact surface of each edge 12a with the resin part 20 is expanded in the Y-axis direction. As a result, in the composite member 1, the restraining force in the X-axis direction applied from the joint surface 11 to the resin part 20 is increased, improving the joint strength against a force in the sliding direction along the X-axis applied between the metal part 10 and the resin part 20.

[0026] In addition, by configuring the uneven shape of each edge 12a of each groove 12 on the joint surface 11 of the metal part 10 to be undulating not only in the Z-axis direction but also in the X-axis direction, an anchor effect is obtained as the resin part 20 enters each recess 12c of each edge 12a in the X-axis direction. As a result, in the composite member 1, the anchor effect of each recess 12c of each edge further improves the joint strength against a force in the sliding direction along the Y-axis applied between the metal part 10 and the resin part 20.

[0027] Thus, in the composite material 1, the action of the multiple grooves 12 provided on the joint surface 11 of the metal part 10 improves the joint strength against forces applied between the metal part 10 and the resin part 20 in any of the X-axis direction, Y-axis direction, and Z-axis direction. Therefore, in the composite material 1, high joint strength is likely to be obtained at the joint surface 11 of the metal part 10 provided with the multiple grooves 12, regardless of the direction of force applied between the metal part 10 and the resin part 20 joined to the joint surface 11. Furthermore, in the composite material 1, high vibration resistance is likely to be obtained by providing high joint strength between the metal part 10 and the resin part 20 against forces in all directions.

[0028] In the composite member 1 according to this embodiment, in a cross section cut along an XZ plane perpendicular to the Y axis, the length of the joint surface 11 in a range of a predetermined dimension in the X-axis direction is preferably 150% or more of the predetermined dimension. In other words, a rectangular region having four sides parallel to the X-axis and Z-axis of a predetermined dimension is defined in the X-axis direction in the cross section, and the length along the uneven shape of the cross section of the joint surface 11 appearing as a meandering curve in the region is preferably 150% or more of the dimension in the X-axis direction of the region. Note that in the composite member 1, from the viewpoint of forming a plurality of grooves 12 of appropriate shapes in the joint surface 11 of the metal part 10, the ratio of the length of the joint surface 11 to the above-mentioned predetermined dimension is preferably kept to less than 450%.

[0029] With this configuration, in the composite material 1, the contact surface 11 on which the multiple grooves 12 of the metal part 10 are provided is expanded in the direction perpendicular to the Y axis by 1.5 times or more compared to a configuration in which the contact surface is a plane parallel to the XY plane. This makes it easier to obtain higher joint strength between the metal part 10 and the resin part 20 in the composite material 1. In this embodiment, the "predetermined dimension" is 2.0 mm or more when converted into the actual size of the composite material 1.

[0030] The length of the bonding surface 11 in the cross section of the composite member 1 as described above can be evaluated as follows. Microscope used: Scanning electron microscope S-3400N (Hitachi High-Tech) Observation conditions: Backscattered electron image (BSE) observation, observation magnification 50x Image analysis Software used: Image-Pro (Hakuto) Applied image processing functions: Filter function (low-pass filter) Measurement items and areas: "Perimeter" and "Fractal dimension" evaluate the length of the joint surface 11 as the fractal dimension (degree of unevenness) of the contour of the object Specifically, the length of the joint surface 11 can be obtained by the following image analysis. (1) Specify the measurement range. (Specify the ROI region of interest to the joint surface 11.) (2) Apply a low-pass filter to remove minute noise. (3) The analysis image is binarized based on its brightness, and the target joint surfaces 11 are counted and detected. (4) In order to eliminate the influence of tiny white areas (metallic areas) in the image, the lower limit of the area value is set to 0.05 mm 2 and set it to be excluded from the measurement range. (5) Set the measurement item to "perimeter length," select "fractal dimension" for evaluating the degree of unevenness, and measure the length of the joint surface 11 within the ROI_region of interest.

[0031] [Method of manufacturing composite material 1] (Brief explanation) Fig. 6 is a flowchart showing a method for manufacturing the composite material 1 according to this embodiment. The method for manufacturing the composite material 1 includes step S01 (preparation of raw material), step S02 (laser treatment), and step S03 (insert molding). The method for manufacturing the composite material 1 will be described below along Fig. 6 with appropriate reference to Figs. 7 to 9.

[0032] (Step S01: Prepare raw materials) In step S01, a raw metal M constituting the metal part 10 and a raw resin constituting the resin part 20 are prepared as raw materials for the composite member 1. The raw metal M can be prepared, for example, as a metal structure formed of any metal and processed into a shape corresponding to the metal part 10. The raw resin can be prepared, for example, as a powder or pellets mainly composed of any thermoplastic resin capable of being insert molded. Various fillers to be mixed with the raw resin are prepared as necessary.

[0033] (Step S02: Laser processing) In step S02, the raw metal M prepared in step S01 is subjected to laser processing to produce a metal member 110. Figure 7 shows the process of this step. In this step, laser processing is performed on the joining surface 111 of the raw metal M, with the main scanning direction of the laser D being the Y-axis direction and the sub-scanning direction of the laser D being the X-axis direction. That is, in this step, grooves 112 are formed one by one along the X-axis direction while the laser D is reciprocatingly scanned in the Y-axis direction on the joining surface 111 of the raw metal M.

[0034] The conditions for irradiating the laser D to the joining surface 111 of the raw metal M are determined so that a plurality of grooves 12 having the above-mentioned configuration are obtained on the joining surface 11 of the metal part 10 of the composite member 1 after manufacture. For example, the laser processing in this step can be performed under conditions in which only the edge 112a of the groove 112 is moderately partially melted by irradiation with the laser D so that a pair of edges 12a having the above-mentioned uneven shape is obtained in each groove 12 of the composite member 1 after manufacture. The laser D used in this step may be either a continuous wave laser or a pulsed laser, but is preferably a pulsed laser capable of optimizing the three-dimensional shape of the edge 112a of the groove 112 by the oscillation frequency.

[0035] In this step, the ratio Sa / B of the average depth Sa to the average width B of each groove 112 of the metal member 110 is preferably 0.2 or more, more preferably 0.5 or more. In addition, the ratio Sa / C of the average depth Sa of each groove 112 to the center line distance C that defines the interval between the multiple grooves 112 in the metal member 110 is preferably 0.02 or more, more preferably 0.10 or more. As a result, the depth of each groove 12 becomes sufficiently large at the joint surface 11 of the metal part 10 of the composite member 1 after manufacture, making it easier to obtain a higher joint strength between the resin part 20. In addition, in order to make it difficult for the raw material resin to enter the multiple grooves 112 to be hindered, the average width B of each groove 112 is preferably 20μ or more, and the ratio Sa / B is preferably 1.5 or less. Furthermore, from the viewpoint of processing the multiple grooves 112 into an appropriate shape, it is preferable to keep the ratio Sa / C to 0.75 or less.

[0036] For each groove 112, the average depth Sa is calculated as the average value of the depth S in the Z-axis direction along the Y-axis direction. The depth S at each portion of each groove 112 along the Y-axis direction is calculated as the distance along the Z-axis direction between the highest portion in the Z-axis direction at a pair of edges 112a and the deepest portion in the Z-axis direction at a center portion 112b, as shown in Fig. 8. In other words, the depth S at each portion of each groove 112 along the Y-axis direction is the maximum dimension in the Z-axis direction of the outline of each groove 112 that appears in a cross section of the metal member 110 along the YZ plane.

[0037] The average width B of each groove 112 is obtained as the distance along the X-axis direction between a pair of straight lines L1 along the Y-axis direction passing through the innermost parts of a pair of edges 12a in the X-axis direction in an image captured from the Z-axis direction of the joint surface 111 shown in Fig. 9. Also, for each groove 112, a straight line along the Y-axis direction that bisects the area between the pair of straight lines L1 is defined as a center line L2. The center line distance C of the multiple grooves 112 is obtained as the distance along the X-axis direction between the center lines L1 of adjacent grooves 112.

[0038] The average width B of each groove 112 on the joining surface 111 of the metal member 110, the average depth Sa of each groove 112, and the distance C between center lines of the plurality of grooves 112 are obtained by a shape analysis of the joining surface 111 after the laser treatment of the metal member 110. The shape analysis of the joining surface 111 of the metal member 110 can be performed as follows. Analytical equipment: Nano 3D optical interference measurement system VS1800 (Hitachi High-Tech) Objective lens: 20x (working distance 4.7mm) Measurement field of view: 0.55mm (when using 20x objective lens) ·Vertical resolution / spatial resolution: 0.01nm / 350nm Average depth Sa (μm) calculation: Compliant with ISO 25178

[0039] (Step S03: Insert molding) In step S03, the raw resin prepared in step S01 is insert molded using the metal member 110 obtained in step S02 as an insert material. This results in a composite member 1 in which the raw resin is bonded to the bonding surface 111 of the metal member 110. The conditions for the insert molding can be appropriately determined so that the resin portion 20 adheres closely to the shapes of the multiple grooves 12 on the bonding surface 11 of the metal portion 10.

[0040] [Application of composite material 1] The composite member 1 according to this embodiment can be used for various applications. Fig. 10 is a diagram showing an electronic device case 1a as an example of the composite member 1. The electronic device case 1a is provided with an internal space K for accommodating an electronic device. The electronic device case 1a has high vibration resistance and is therefore particularly suitable for accommodating in-vehicle electronic devices. Examples of in-vehicle electronic devices that can be accommodated in the internal space K of the electronic device case 1a include inverters and millimeter wave radars.

[0041] The electronic device case 1a has a support portion 10a which is a metal portion 10, and a wall portion 20a which is a resin portion 20. The wall portion 20a is a frame that surrounds the periphery of the internal space K on the flat support portion 10a. The support portion 10a is provided with a joint surface 11a to which the wall portion 20a is joined over its entire periphery. In the electronic device case 1a, heat generated by an electronic device accommodated in the internal space K can be efficiently released to the external environment while being diffused in the support portion 10a made of metal.

[0042] The material forming the wall 20a of the electronic device case 1a is preferably provided with the ability to suppress the transmission of electromagnetic waves, that is, with at least one of electromagnetic wave absorption and electromagnetic wave reflection properties. This makes it difficult for electromagnetic waves to affect each other between the internal space K and the external environment in the electronic device case 1a, thereby achieving high electromagnetic compatibility (EMC).

[0043] The material forming the wall 20a of the electronic device case 1a can be, for example, obtained by mixing an electromagnetic wave absorbing filler into a resin to obtain electromagnetic wave absorption, or obtained by mixing an electromagnetic wave reflecting filler into a resin to obtain electromagnetic wave reflection. Examples of the electromagnetic wave absorbing filler include magnetic powder, conductive material powder, carbon powder, inorganic fine particles, and metal wires. Examples of the electromagnetic wave reflecting filler include metal powder, conductive fiber, and carbon fiber.

[0044] [Other embodiments] Although the embodiments of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments, and various modifications can be made. For example, the grooves 12 provided on the joint surface 11 of the metal part 10 of the composite material 1 are not limited to a configuration extending linearly, and may be configured to extend in a curved shape. In addition, the overall shape of the joint surface 11 of the metal part 10 of the composite material 1 does not have to be flat, and may be curved.

[0045] [Example] Hereinafter, an embodiment of the present invention will be described. Note that the configuration of the following embodiment is merely one example of the configuration of the present invention, that is, the configuration of the present invention is not limited to the configuration of the following embodiment.

[0046] (Brief explanation) In each example, a sample of the composite material 1 according to the above embodiment was prepared, and the bonding strength of the sample was evaluated. Fig. 11 is a perspective view of the sample of the composite material 1 prepared in each example. Each sample was a overlapping test piece (Type B) in accordance with ISO19095-2:2015, and had a configuration in which a metal part 10 of 18 mm x 45 mm x 1.5 mm and a resin part 20 of 10 mm x 45 mm x 3 mm were bonded at a bonding surface 11 of 10 mm x 5 mm.

[0047] In each example, the following condition 1 or condition 2 was used as the condition for the laser treatment of the joining surface 111 of the metal member 110 for producing each sample. <Condition 1> Laser oscillator: RFL-P100Q / A10 / 250 / 2 (Raycus) Laser type: Pulsed fiber laser (nanosecond laser with a pulse width of 50 to 130 ns at 20 kHz) Laser output: 100% (measured at processing position: 87.0 W) Laser frequency: 100kHz Galvano scanner speed (scanning speed): 500mm / sec Galvano scanner Number of scans: 1 <Condition 2> Laser type: Pulsed fiber laser Laser power: 60W Laser frequency: 100kHz Pitch width: 0.1mm - Machining speed per pitch: 500mm / sec. or 1000mm / sec

[0048] The bonding strength of each sample was evaluated by a tensile test. An AGX-20KNVD (manufactured by Shimadzu Corporation) was used as the tensile tester. The tensile speed was 10 mm / min in accordance with ISO19095-2:2015. The test environment temperature was room temperature (approximately 23°C). Specifically, in the tensile test, the tensile load applied between the metal part 10 and the resin part 20 of each sample was increased, and the tensile load at which the sample broke was taken as the bonding strength.

[0049] In each table below, the tensile direction in the tensile test for evaluating the bonding strength of each example is indicated by "X" or "Y". In examples where the tensile direction is "X", the tensile direction is perpendicular to each groove 12 on the joint surface 11 of the sample, that is, a plurality of grooves 12 perpendicular to the tensile direction are formed on the joint surface 11 of the sample. In addition, in examples where the tensile direction is "Y", the tensile direction is along each groove 12 on the joint surface 11 of the sample, that is, a plurality of grooves 12 along the tensile direction are formed on the joint surface 11 of the sample.

[0050] (Examples 1-1 to 1-14) In all of Examples 1-1 to 1-14, the resin part 20 was formed of PBT mixed with an electromagnetic wave absorbing filler. In all of Examples 1-1 to 1-10, the metal part 10 was formed of an aluminum alloy (A5052), and in all of Examples 1-11 to 1-14, the metal part 10 was formed of stainless steel (SUS304). In Examples 1-1 to 1-14, the laser treatment on the joint surface 111 of the metal member 110 was performed under Condition 1 so that the average depth Sa of the grooves 112, the average width B of the grooves 112, and the center line distance C of the plurality of grooves 112 were configured as desired. In Examples 1-9 and 1-10, the laser frequency was changed to 200 kHz, and the galvano scanner speed (scanning speed) was changed to 1000 mm / sec. In all of Examples 1-1 to 1-14, a sample of the composite member 1 in which the above-mentioned uneven shape was provided on a pair of edges 12a of each groove 12 on the joint surface 11 was obtained.

[0051] Table 1 shows the average depth Sa of the grooves 112, the average width B of the grooves 112, the center line distance C of the grooves 112, the ratio Sa / B, and the ratio Sa / C in the metal members 110 used in Examples 1-1 to 1-14. As shown in Table 1, in Examples in which the ratio Sa / B was 0.2 or more and the ratio Sa / C was 0.02 or more, samples with high bonding strength of approximately 10 MPa or more were obtained. Furthermore, no significant difference was observed in the bonding strength of the samples due to differences in the tensile direction ("X" or "Y").

[0052] [Table 1]

[0053] (Examples 2-1 to 2-9) In all of Examples 2-1 to 2-9, the resin part 20 was formed of PEEK. In all of Examples 2-1 to 2-6, the metal part 10 was formed of aluminum alloy (A5052), and in all of Examples 2-7 to 2-9, the metal part 10 was formed of stainless steel (SUS304). In all of Examples 2-1 to 2-9, laser processing was performed on the joint surface 111 of the metal member 110 under Condition 1 so that the average depth Sa of the grooves 112, the average width B of the grooves 112, and the center line distance C of the plurality of grooves 112 were configured as desired. In all of Examples 2-1 to 2-9, a sample of the composite member 1 was obtained in which the above-mentioned uneven shape was provided on a pair of edges 12a of each groove 12 on the joint surface 11.

[0054] Table 2 shows the average depth Sa of the grooves 112, the average width B of the grooves 112, the center line distance C of the grooves 112, the ratio Sa / B, and the ratio Sa / C in the metal members 110 used in Examples 2-1 to 2-9. As shown in Table 2, in Examples in which the ratio Sa / B was 0.2 or more and the ratio Sa / C was 0.02 or more, samples with high bonding strength of approximately 10 MPa or more were obtained. Furthermore, no significant difference was observed in the bonding strength of the samples due to differences in the tensile direction ("X" or "Y").

[0055] [Table 2]

[0056] (Examples 3-1 to 3-4) In all of Examples 3-1 to 3-3, the metal part 10 was formed of aluminum alloy (A5052), and the resin part 20 was formed of PBT mixed with carbon fiber as an electromagnetic wave reflective filler. In Example 3-4, the metal part 10 was formed of stainless steel (SUS304), and the resin part 20 was formed of heat-resistant polyamide (PA9T) mixed with glass fiber as a filler for improving strength. In Examples 3-1 to 3-4, laser processing was performed on the joint surface 111 of the metal member 110 under Condition 1 so that the average depth Sa of the grooves 112, the average width B of the grooves 112, and the center line distance C of the plurality of grooves 112 were configured as desired. In all of Examples 3-1 to 3-4, a sample of the composite member 1 was obtained in which the above-mentioned uneven shape was provided on a pair of edges 12a of each groove 12 on the joint surface 11.

[0057] Table 3 shows the average depth Sa of the grooves 112, the average width B of the grooves 112, the center line distance C of the grooves 112, the ratio Sa / B, and the ratio Sa / C in the metal members 110 used in Examples 3-1 to 3-4. As shown in Table 3, in all of the Examples, high values ​​were obtained for the ratio Sa / B and the ratio Sa / C, and samples with high bonding strength exceeding 30 MPa were obtained.

[0058] [Table 3]

[0059] (Examples 4-1 to 4-4) In all of Examples 4-1 to 4-4, the resin part 20 was formed of PBT mixed with an electromagnetic wave absorbing filler. In all of Examples 4-1 to 4-3, the metal part 10 was formed of an aluminum alloy (A5052), and in Example 4-4, the metal part 10 was formed of stainless steel (SUS304). In Example 4-1, the laser treatment was performed on the joint surface 111 of the metal member 110 under condition 1 so that the average depth Sa of the grooves 112, the average width B of the grooves 112, and the center line distance C of the plurality of grooves 112 were configured as desired. In Examples 4-2 to 4-4, the laser treatment was performed on the joint surface 111 of the metal member 110 under condition 2 so that the average depth Sa of the grooves 112, the average width B of the grooves 112, and the center line distance C of the plurality of grooves 112 were configured as desired. In each of Examples 4-1 to 4-4, a sample of the composite material 1 in which the above-described uneven shape was provided on a pair of edges 12a of each groove 12 on the joining surface 11 was obtained.

[0060] Table 4 shows, for Examples 4-1 to 4-4, the ratio of the length of bonding surface 11 to a predetermined dimension within a predetermined range in the in-plane direction of bonding surface 11 in a cross section of the sample perpendicular to the extension direction of groove portion 12. As shown in Table 4, samples with sufficiently high bonding strength were obtained in all Examples, and there was a tendency for the bonding strength to increase as the ratio of the length of bonding surface 11 increased.

[0061] [Table 4]

[0062] (Vibration test) A vibration test was carried out on the samples according to the above-mentioned Examples 1-1, 1-2, 2-1, and 2-2. The vibration test was carried out under the conditions of a vibration frequency of 33 Hz and a vibration acceleration of 4.5 G. In the vibration test, the vibration was applied in three axial directions (upward / downward, leftward / rightward, and frontward / rearward) for a total of 6 hours, 2 hours in the upward / downward direction, 2 hours in the leftward / rightward direction, and 2 hours in the frontward / rearward direction. Table 5 shows the bonding strength of the samples according to Examples 1-1, 1-2, 2-1, and 2-2 before and after the vibration test. It was found that the change in bonding strength before and after the vibration was less than 5% for all samples, and high vibration resistance was obtained.

[0063] [Table 5] [Explanation of symbols]

[0064] 1. Composite material 10...Metal part 11...Joint surface 12...Groove 12a...Edge 12b…Central part 12c…Concave 20…Resin part

Claims

1. a metal part having a joint surface on which a plurality of grooves are arranged, each of the plurality of grooves having a pair of edges that rise and fall in a direction perpendicular to the joint surface and in an in-plane direction along an extension direction of the groove; a resin portion directly bonded to the bonding surface; A composite member comprising:

2. 2. The composite member according to claim 1 , In a cross section of the composite member perpendicular to the extending direction, the length of the joining surface within a range of a predetermined dimension in the in-plane direction is 150% or more of the predetermined dimension. Composite material.

3. The composite member according to claim 1 or 2, The metal portion is made of any one of aluminum, iron, and copper as a main component. Composite material.

4. The composite member according to claim 1 or 2, The resin portion is mainly composed of a thermoplastic resin. Composite material.

5. The composite member according to claim 1 or 2, The resin portion contains a component that suppresses the transmission of electromagnetic waves. Composite material.

6. 6. The composite member according to claim 5, Configured as a case for in-vehicle electronic devices Composite material.

7. A raw material metal having a joining surface and a raw material resin containing a thermoplastic resin as a main component are prepared; By providing a plurality of grooves arranged on the joining surface by laser processing, a metal member is produced in which each of the groove portions constituting the plurality of groove portions has a pair of edges that rise and fall in a direction perpendicular to the joining surface and in an in-plane direction along an extension direction of the groove portion; A composite member is manufactured by insert molding the raw resin using the metal member as an insert material, in which a resin portion is directly bonded to the bonding surface. A method for manufacturing a composite component.

8. A method for producing a composite member according to claim 7, comprising the steps of: The metal member is manufactured so that the ratio Sa / B of the average depth Sa to the average width B of each of the plurality of grooves is 0.2 or more. A method for manufacturing a composite component.

9. A method for producing a composite member according to claim 7 or 8, The metal member is manufactured so that a ratio Sa / C of an average depth Sa of each of the plurality of grooves to a center line distance C of the plurality of grooves is 0.02 or more. A method for manufacturing a composite component.

Citation Information

Patent Citations

  • Manufacturing method of composite molding

    JP2016064659A